Government regulations, external financing and economic performance: The case of Mexico - Uwe Corsepius (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
During the 1970s and early 1980s Mexico, like many other Latin American countries, relied to a large extent on foreign capital in financing public and private expenditures. While the annual inflow of debt was always larger than that of foreign direct investment (fdi), the relative importance of both types of capital varied substantially over the 1970-81 period. The ratio of debt over fdi inflows was as low as 2.6 in the 1970-74 period. It increased to 6.7 during the years 1975-77 and averaged 5.0 in 1978- 81 . In the same three sub-periods, the real growth rate of gross domestic product dropped from an average of 6.8 per cent to 4.4 per cent before it increased again to 8.4 per cent. Hence, relatively good economic performance coincided with relatively large fdi inflows.
Keywords: 330; Prinzipal-Agent-Theorie; Entwicklungsfinanzierung; Direktinvestition; Auslandsverschuldung; Wirtschaftswachstum; Mexiko